PENGARUH CASH CONVERSION CYCLE, INVENTORY TURNOVER, AVERAGE PAYMENT PERIOD, CASH TURNOVER DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Sektor Trade, Services & Investment Periode 2012-2015) - MIFTAHUL ULUM, MUH. (Jurnal Ilmu Manajemen (JIM), 2017)
The main purpose of this research is to test the influence of Cash Conversion Cycle, Inventory Turnover, Average Payment Period, Cash Turnover and Leverage on firm’s profitability. This type of research is a quantitive and conclusive research in the form of causality by using purposive sampling methods, so that obtained 60 companies that meet the criteria. The object of this research are Trade, Services, and Investment’s companies that listed on Indonesia Stock Exchange period 2012 – 2015. The data used are secondary data obtained from annual report, financial report, and Summary of company performance. The data analysis technique used multiple linear regression analysis and using IBM SPSS version 23. The result of this study found that cash turnover and leverage negatively effect on firm profitability. While cash conversion cycle, inventory turnover, and average payment period positively on firm profitability. Based on the findings in this research, can be a consideration for the company to give more attention to the factor of Cash Turnover and Leverage factors that have a negative effect on the profitability of the company. With information about the factors that affect profitability can be used as the basis of investor decisions to make investment and become the next research reference to involve other variables that are considered more influential on profitability with different models. Keywords: profitability, cash conversion cycle, inventory turnover, average payment period, cash turnover, leverage